Nursing diagnoses, results, and interventions in the care for Covid-19 patients in critical condition - Menezes, Harlon França de; Moura, Jéssica Lima; Oliveira, Sylvia Silva de; Fonseca, Michelle Carneiro; Sousa, Paulino Artur Ferreira de; Silva, Richardson Augusto Rosendo da (Revista da Escola de Enfermagem da USP, 2021)
Objective: To develop and validate a terminological subset of the International Classification for Nursing Practice for COVID-19 patients in critical care. Method: This is a methodological study, which followed the guidelines of the Brazilian method, using the Basic Human Needs as a theoretical model. Content validation was performed by 25 specialist nurses using the Delphi technique. Results: A total of 73 diagnoses and their respective nursing results were prepared. Of these, 62 statements had a Content Validity Index ≥ 0.80, with the need for oxygenation having the highest number of statements. Of the 210 nursing interventions developed, and after suggestions from experts, 150 interventions reached an index ≥ 0.80 and comprised the terminological subset. Conclusion: The terminological subset developed showed statements that were validated by specialist nurses and, therefore, are relevant to the nurse's clinic in the critical care scenario associated with Covid-19.